EFEK KEMANDIRIAN KEUANGAN, BELANJA MODAL DAN DANA ALOKASI UMUM TERHADAP PERTUMBUHAN EKONOMI - Muakhir Fitrah; Jannati Tangngisalu; Syamsul Alam (Al-Buhuts, 2024)
This research aims to test whether financial independence, capital expenditure and general allocation funds influence economic growth in City Districts in South Sulawesi Province. Data collection methods use documentation and library studies. Library studies are a technique for obtaining information through notes, literature, documentation and so on. This type of research data is quantitative data obtained from secondary data, namely data collected from existing sources. This research uses panel data, namely by combining data across regions (cross-section) of 24 districts/cities and across time (time series) during 2020 to 2022. The population in this study is districts and cities in South Sulawesi Province, sampling method using the saturated sample method. So the number of samples is 24 districts/cities in South Sulawesi. The number of samples is (24 districts/cities x 3 years) = 72 samples. The analysis method uses a multiple regression analysis method using panel data with the help of Microsoft Excel and E-views software programs. The results of the research show that financial independence has a positive and significant effect on economic growth in city districts in South Sulawesi Province, capital expenditure has a negative and significant effect on economic growth in city districts in South Sulawesi Province, and general allocation funds have a positive and insignificant effect on economic growth. in city districts in South Sulawesi Province.